HIDDEN ACTION IN THE CASE OF TAX DISPUTES IN INDONESIA - Dwiputri, Inayati Nuraini (Journal of Indonesian Economy and Business, 2012)
This research aimed to conduct a study for tax dispute cases in Indonesia, which refersÂ to the behavior of the Supreme Courtâs verdict and indication of hidden action done byÂ taxpayer in an effort to win tax disputes and to analyze the taxation regulations especiallyÂ on the case of tax disputes. The research data are Supreme Courtâs verdicts 2004-2010 onÂ the tax disputes cases.This research uses descriptive and logistic regression analysis. The result shows theÂ Supreme Courtâs verdict has different way of treating tax year, the length of processingdisputes, and the difference of calculation between taxpayers and tax apparatus. TheÂ analysis indicates that hidden action is done by taxpayers in an effort winning the taxÂ disputes. The higher difference of calculation, the higher probability for taxpayers to winÂ the tax disputes. The longer processing time of tax disputes on the level of Supreme CourtÂ the higher probability for taxpayers winning the disputes. This indicates the publicÂ functionaryâs involvement in hidden action by taxpayers. The hidden action done can be inÂ the form of corruption, collusion, and bribery. The analysis of taxation regulationÂ indicates that Indonesian taxation regulations have not been implemented well anddeviation is still found.From this research result and the reference to the previous researches, it is identifiedÂ that the Indonesian government is required to do things such as: 1) promoting the qualityof tax apparatus either intellectually or through moral behavior; 2) promoting the obedienceÂ of taxpayer by promoting the benefits of paying tax especially for taxpayers; 3)Â inviting citizens/societies and social institution to fight against corruption; 4) promotingÂ the obedience to the taxation regulation for taxpayers and tax apparatus; 5) designing aÂ better taxation institution; 6) shortening the time for the process of disputes.Keywords: hidden action, corruption, the Supreme Courtâs verdict, taxpayers.